Analysis of factors controlling maize yield response to hairy vetch and to nitrogen fertilization after hairy vetch - Carciocchi, Walter Daniel (2023)
Context or problem: Several agricultural producers around the world are adopting hairy vetch (HV) (Vicia villosa Roth) inclusion in the crop sequence before maize (Zea mays L.). To date, it is not clear which factors control maize yield response to HV and to nitrogen (N) fertilization in HV-maize sequences. Objective or research question: We aimed to i) explore the variability of maize grain yield response to HV and to N fertilization (after HV) and ii) analyze the factors that define the mentioned variability.Methods: We conducted 25 field studies in the southeastern Argentinean Pampas, exploring a wide range of conditions related to HV management and edaphoclimatic properties. We evaluated four treatments resulting from the combination of two preceding conditions, i) HV and ii) bare fallow (BF), and two situations of N fertilization on maize i) with N and ii) without N. Results: We observed that, without N fertilization, maize yield significantly increased by 1846 kg ha−1 due to HV, and the response was significant in 52% of the studies. Low-yield environments exhibited a greater yield response to HV than high-yield environments (2792 vs. 989 kg ha−1). Nitrogen supply from HV was the main factor determining variations in grain yield response to HV, although factors other than N (e.g., water availability, changes in soil physical and biological properties) presented a significant effect (avg. 366 kg ha−1). Specifically, the N supply from HV and soil N availability explained maize yield response to HV. We calibrated and validated a model from these variables that explained 61% of the variability in yield response to HV. We also observed that N fertilization after HV increased maize yield, on average, by 1301 kg ha−1 (significant in 36% of the sites), which was almost half of the response to N fertilization after BF (avg. 2782 kg ha−1, significant in 68% of the sites). Maize yield response to N after HV was explained by both the maize N demand and the N supply from HV. Conclusions: Nitrogen supply from HV and soil N availability defined maize grain yield response to HV. Including HV in crop sequences before maize reduced its fertilizer-N requirement. Maize N demand and N supplied from HV explained the grain yield response to fertilizer-N. Implications or significance: The information and models provided will allow producers to assess the convenience of including HV before maize in the crop sequence and to adjust N fertilization rates, avoiding yield penalties and negative environmental externalities.